MOTIVASI PENGUNJUNG BERWISATA KE OBJEK WISATA PANTAI AIR MANIS KOTA PADANG - Darmadi, Riki; Waryono, Waryono; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research aims to determine the motivation of visitors to the touristattractions in Pantai Air Manis viewed from 2 indicators, namely, internal factors andexternal factors. This research is a quantitative descriptive research with a surveymethod. The population of this research is the domestic visitors who travel to theattractions of Pantai Air Manis. The sampling technique is non probability sampling,using incidental sampling. The number of samples in this research are amount to 98people. Technique of collecting data is done by using questionnaire with Likert scalethat has been tested the validity and reliability. Furthermore, the data were analyzedthrough descriptive analysis using SPSS 16.00 program. The results of this researchshowed that the motivation of visitors to the tourist attractions in Pantai Air ManisPadang City as a whole is in good category with an average value of 67.74. Whilebased on the indicators, (1) internal factors are in good category with an averagevalue of 34.07. (2) external factors are in good category with an average value of33.67.Keywords: Visitors Motivation, Tourist Attraction1Prodi Manjemen